Analisis Faktor-Faktor Yang Mempengaruhi Kepuasan Pengguna Jasa Industri Konveksi Pada Kecamatan Negeri Besar Kabupaten Way Kanan - Yateno, Yateno; Ratmono, Ratmono; Nurriati, Nia (Universitas Muhammadiyah Metro, 2023)
The factors that influence consumer satisfaction in the State Besar District, Way Kanan Regency which will be examined by the author include product quality, price, and service. This study aims to analyze the effect of product quality, service quality, and pricing on user satisfaction of the convection industry in Negeri Besar District, Way Kanan Regency. This type of research uses case study research. The research method used in this study is a descriptive method with a quantitative approach. The sample in this study was 65 respondents who were taken by accidental sampling technique. Data were collected using a questionnaire sheet and analyzed using Multiple Linear Regression Analysis. The results showed that the quality of the product obtained a tcount value of 2,497> ttable 2. 000 and a significant value of 0.018 <0.05, meaning that product quality affects service user satisfaction. The service obtained a value of tcount 2,719 > ttable 2,000 and a significant value of 0.009 < 0.05, meaning that service has an effect on service user satisfaction. The price has a tcount value of 0.893 < ttable 2,000 and a significant value of 0.375 > 0.05, meaning that the price has no effect on service user satisfaction. While the results of the F test (simultaneous) obtained Fcount of 41.230 and Ftable value of 2.760, meaning that product quality (X1), service (X2), price (X3) simultaneously affect the dependent variable,namely service user satisfaction (Y). 65.3% of the role of the variable quality of product,service, price is able to explain the variable of service user satisfaction, while 34.7% isinfluenced by other factors not examined in this study.